Data for: Timestamped list-mode data from coincidence γ-ray spectrometry with HPGe detectors on air-filter samples - Andersson, Peter; Göök, Alf; Andersson-Sundén, Erik; Jarl Holm, Stefan; Jansson, Peter (Uppsala University, 2025)
This dataset contains raw ROOT formatted timestamped list-mode data obtained using an array of HPGe detectors for the purpose of testing coincidence spectrometry, in the context of measurements on air filter samples. The data can be read with ROOT version 6.32.08.

In addition, the dataset contains the same data converted to CSV format. The conversion was made by an example C++ code that is also provided in the dataset. The C++ code can be compiled by a compiler adhering to the standard ISO/IEC 14882:2017 (i.e, ”C++17”).

Detta dataset innehåller ROOT-formaterade tidsstämplade list-mode data insamlade med en array av HPGe-detektorer i syfte att testa koincidensspektrometri, i en kontext av mätningar på luftprover. Datat kan läsas med ROOT version 6.32.08.

Dessutom innehåller detta dataset samma data konverterad till CSV-format. Konverteringen gjordes med en exempel C++-kod som också tillhandahålls med datasetet. C++-koden kan kompileras med en kompilator som följer standarden ISO/IEC 14882:2017 (i.e, ”C++17”).
Data för: Timestamped list-mode data from coincidence γ-ray spectrometry with HPGe detectors on air-filter samples
Keywords: ARMS CONTROL; VAPENKONTROLL; nuclear test; kärnvapenprov; bismuth oxides; compton effect; gamma ray spectrometers; radiation detectors; radionuclides; semiconductor detector; halvledardetektor; anti-Compton shielding; anti-Compton-skärmning; Radionuclide monitoring; Radionuklidmonitorering; Gamma Coincidence Spectrometry; Gammakoincidensspektrometri; high purity germanium detector; högren germanium-detektor; BGO detector; BGO-detektor; Subatomic Physics; Subatomär fysik; Engineering and Technology; Teknik